A escola de canto lírico em Goiânia: fundamentos e práticas pedagógicas - Felipe, Mábia Regina Aires Mendes (2013)
The focus of this research is the basics of the vocal pedagogy developed in Goiânia, Goiás, Brazil. It’s goal is to identify, select and analyze the pedagogical practices of the voice teachers. The main authors who support this work are Behlau (2001), Miller (1996; 2002), Ott & Ott (2006) and ware (1998). This is a qualitative research, based on the phenomenological method (FREIRE, 2007). Therefore, multiple forms of investigation were used to collect data such as revision of literature, interview, questionnaires and observations. The pedagogical approaches of the teachers were compared both to the singing literature and the teaching conceptions of the Italian, German and French schools, named as National Schools of Singing, and to the international principles on Singing. The observations allowed the analysis of the theory-practice relation developed in the context of the voice lessons, according to the methodologies of the national schools and the Internationalism in singing, reporting the teaching practices to bases of the learning cognitive process. Although the methodology of each teacher may be peculiar, the results show that their approaches are somehow related to the National Schools of Singing. However, the teachers demonstrate to be less engaged with any of these schools. They base their methodologies on the studies of vocal physiology and a wide variety of vocal repertoire according to the tonal ideals of International Singing, aiming a better quality of singing.